La enseñanza de la física a través de módulos experimentales - Avendaño, Ronald; Lancheros, Wilson; Castiblanco, Olga; Arcos, Fabio Omar (Góndola, enseñanza y aprendizaje de las ciencias, 2012)
This proposal for teaching and learning physics was developed in two private high school institutions in Bogotá, Colombia, with students between 13 and 18 years old. We research different educational possibilities throughout experimental work in the classroom. We planned, applied and analyzed five modules for the laboratory, each one with small goals to achieve an overall objective. The process was designed according to the proper characteristics about physics topics and assembly difficulties. The modules were about; mechanics, electricity, thermodynamics, fluid mechanics and waves, by means of 5 modules that were titled: Tractor mechanic, Heat engine, Wind tunnel, Van Der Graff generator and Doppler effect. In general, they consist of; design, construction, operation, and explanation. We observed active participation of students in their learning process, interdisciplinary work, and reflections on science and technology impact on the society.